2014
DOI: 10.7883/yoken.67.399
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus Infection in Children with Cystic Fibrosis

Abstract: SUMMARY: Nasopharyngeal swabs obtained from 78 pediatric patients with cystic fibrosis (CF), including 47 with acute pulmonary exacerbation and 31 in a stable clinical condition, were evaluated for 17 respiratory viruses. Human rhinovirus (HRV) was the most frequently detected virus in patients with pulmonary exacerbation and in those who were clinically stable (21.3z vs. 12.9z; P = 0.52). HRV-A was the main RV detected in patients with pulmonary exacerbations. However, no prevalence of particular HRV-A subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
2
12
1
Order By: Relevance
“…Esposito et al showed that human rhinovirus is the most commonly associated viral infection with CF patients. Rhinovirus detection was significantly associated with the occurrence of CF pulmonary exacerbation [18].…”
Section: Discussionmentioning
confidence: 97%
“…Esposito et al showed that human rhinovirus is the most commonly associated viral infection with CF patients. Rhinovirus detection was significantly associated with the occurrence of CF pulmonary exacerbation [18].…”
Section: Discussionmentioning
confidence: 97%
“…A study by de Almeida and colleagues reported a significant association between RV‐A2 or −C and respiratory exacerbations in children with cystic fibrosis (CF) . We, and others, have previously reported that RV was the most common respiratory virus detected in a cohort of children with CF during their regular clinic visits, however RV was not significantly associated with respiratory exacerbations in these studies . Understanding the impact of respiratory viral infections in children with CF is important in managing and minimising the progression of their disease.…”
Section: Introductionmentioning
confidence: 82%
“…A few studies have used PCR to detect HRV infections in CF patients, but they did not sample during symptom-free episodes or lacked adequate non-CF control groups. [20][21][22][23] Our study adds unique longitudinal data from healthy and diseased children irrespective of complaints, using genotyping of HRV subtypes to distinguish prolonged detection of the same HRV strain from increased infections with different HRV subtypes.…”
Section: Discussionmentioning
confidence: 99%